Synthesis and Optimization of Chitosan Nanoparticles of Shrimp shell as Adsorbent of Pb2+ Ions - Sulistyani Sulistyani; Hasanah H; Wijayanti T (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2017)
Synthesis and optimization of chitosan nanoparticles from shrimp shell as an adsorbent of Pb2+ ions has been done. Chitosan is obtained through several stages, namely deproteinase, demineralization and deacetylation. Deproteinase by using 2 N NaOH solution (a ratio of 1:6 w/v) while stirring at 90 °C for 1 hour. Demineralization by using 1 N HCl solution (a ratio of 1:12 w/v) while stirring at room temperature for 1 hour. Deacetylation by using 50% NaOH solution (a ratio of 1:10 w/v) at 120 °C for 3 hours. Chitosan nanoparticles are obtained by adding a solution of 1% CH3COOH and a few drops of NH3 concentrated at 90 °C to form a white gel is then washed to pH neutral and dried. Characterization of chitosan include analysis of degree of deacetylation by using FTIR and analysis of particle size by using Particle Size Analyzer (PSA). Chitosan nanoparticles was then applied as an adsorbent of lead. Optimization of chitosan as an adsorbent include contact time and pH. Concentration of lead is determined using Atomic Absorption Spectroscopy (AAS). The results showed chitosan synthesis product has a size of 600 nm, so that it can be expressed as nanoparticles with a degree of deacetylation of 62.69%. Chitosan nanoparticles as adsorbent optimum at pH 3 and a contact time of 2 hours with an adsorption capacity of 13,25 mg/g .